Hollows in living trees develop slowly but considerably influence the estimate of forest biomass. (21st September 2015) - Zheng, Zheng; Zhang, Shubin; Baskin, Carol; Baskin, Jerry; Schaefer, Doug; Yang, Xiaodong; Yang, Lianyan
Summary: The decomposition of wood inside living tree hollows influences forest structure and processes. Although the decomposition rate controls the formation of hollows, it has not previously been measured. In an old‐growth subtropical montane evergreen broad‐leaved forest in south‐west China, we measured respiration rates of decaying wood inside living tree hollows, logs (downed tree trunks) and snags (standing dead trees) using infrared CO2 analysis. We compared stem radial growth rates to the horizontal expansion rates of hollows. We also estimated the proportion of hollows to total stem volume and the time required to form nesting hollows. Overall, decaying wood inside living tree hollows had significantly higher wood density but lower a moisture content and respiration rate than logs. Wood moisture content and wood density significantly affected the respiration rates of wood inside tree hollows and logs and snags. The average respiration rate of wood inside tree hollows (0·16 ± 0·02 μmol kg −1 s −1 ) was 49% lower than in logs and 34% lower than in snags. The proportion of stem volume occupied by hollows was 8·0% in this forest. The radial expansion rate of tree hollows was 2·0 mm year −1, which was slightly less than the stem radial growth rate. The rate of vertical expansion of hollows was eight times higher than radial expansion. At these rates, it would require 50–100 years for the formation of hollows large enough for honeybees Apis cerana cerana to nest. We conclude that wood decomposition inside tree hollows is more strongly limited by moisture content than in logs, and a very long time is required to form nesting hollows by decomposition. However, the decomposition of wood inside living tree hollows can considerably influence estimates of stem biomass in old‐growth forests. Abstract : Lay Summary